2014
DOI: 10.1186/s13071-014-0545-z
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic filariasis in Peninsular Malaysia: a cross-sectional survey of the knowledge, attitudes, and practices of residents

Abstract: BackgroundLymphatic filariasis (LF) is a major cause of permanent disability in many tropical and sub-tropical countries of the world. Malaysia is one of the countries in which LF is an endemic disease. Five rounds of the mass drug administration (MDA) program have been conducted in Malaysia as part of the Global Program to Eliminate Lymphatic Filariasis (GPELF) by year 2020. This study investigated the level of awareness of LF and the MDA program in a population living in an endemic area of the country.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…However, despite their knowledge of LF, this did not seem to affect their low compliance with MDA. Studies conducted on populations in endemic areas in India 29 , Tanzania 30 and Malaysia 31 revealed that there were individuals with little or no awareness of LF, even though the areas were considered endemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite their knowledge of LF, this did not seem to affect their low compliance with MDA. Studies conducted on populations in endemic areas in India 29 , Tanzania 30 and Malaysia 31 revealed that there were individuals with little or no awareness of LF, even though the areas were considered endemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study in Malaysia showed that the knowledge regarding filariasis is still low in even in areas endemic for the disease [32]. This was most likely due to a lack of awareness and health education programmes, as some of the endemic areas in Malaysia were in rural areas that were difficult to access via main roads [32,33]. Furthermore, knowledge transfer took place mostly in school programmes and may not have reached the entire community, particularly adults.…”
Section: Knowledge Attitude and Perceptionmentioning
confidence: 99%
“…In Malaysia, LF has been reported with two agents: W. bancrofti and B. malayi (Al-Abd et al 2014). The first report of LF we noted in the literature dates to 1968, but no details were available (Yap et al 1968).…”
Section: Malaysiamentioning
confidence: 99%
“…The earliest report we could find described microfilaria as sub-periodic B. malayi in (Rubis et al 1981). The disease is not widespread in the country, and occurs only in some states of Peninsular Malaysia including Terengganu, Kelantan, Pahang, Selangor, and Johor as well as the very small Sabah and Sarawak regions (Al-Abd et al 2014). In Malaysia, an MDA program is being conducted with the two drugs noted earlier for India.…”
Section: Malaysiamentioning
confidence: 99%
See 1 more Smart Citation